Optimization of Human Resource Planning to Support the Nutritious Free Meal Program as an Effort to Build a Robust National Defense - Sibarani, Tombak L M; Tri, Gunawan; Herman, Juli (Journal of Industrial Engineering & Management Research, 2025)
The Free Nutritious Meal Program is a flagship populist initiative of the Prabowo-Gibran administration, aiming to provide free lunches and milk to school children and pesantren students across Indonesia. This initiative targets over 82.9 million beneficiaries, including toddlers, school children, and pregnant women, with an estimated annual budget of IDR 450 trillion. The program aspires to build a smart, healthy, and competitive generation as a foundation for a resilient national defense. However, its implementation faces significant challenges, including limited human resource (HR) competencies, inefficient logistics, and suboptimal monitoring. Drawing on qualitative methods, this study explores how HR planning optimization can support the success of this program in the context of national defense. The Indonesian Navy (TNI AL), as a component of national defense and maritime logistics, plays a strategic role in addressing HR gaps through comprehensive planning, training, and deployment of skilled personnel, especially in remote coastal areas. Moreover, TNI AL's logistical infrastructure can enhance food distribution efficiency. The study is grounded in national defense law and HR planning theory, emphasizing strategic alignment, competency-based training, and multi-sector coordination. International experiences (the U.S., Finland, Sweden, and others) illustrate the program’s potential to generate economic and health benefits. Ultimately, the integration of effective HR planning, supported by TNI AL’s capabilities, is critical to ensure the program's sustainability and its contribution to national resilience.